2020
DOI: 10.3906/vet-2001-82
|View full text |Cite
|
Sign up to set email alerts
|

Comparing microbiological profiles, bioactivities, and physicochemical and sensory properties of donkey milk kefir and cow milk kefir

Abstract: Consumption of fermented milk products especially kefir is accelerated in the population due to their high nutritional value and other health benefits. These health benefits are rooted in the composition of source material and flora of kefir grains. Therefore, the utilization of different kinds of milk as source material in kefir production directly affects the properties of kefir. In this study, changes in the physicochemical properties, microbiological profiles, antibacterial effects, antioxidant activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
2
9
1
1
Order By: Relevance
“…Donkey milk kefir reduced Klebsiella pneumoniae , Bacillus cereus , and Proteus mirabilis by 8%, 37%, and 58% compared to the kanamycin antibiotic. In contrast, cow milk kefir decreased B. cereus by 12.9% while had the same impact on Proteus mirabilis compared to kanamycin, demonstrating the tremendous antimicrobial potential associated with lactic acid [ 60 , 66 ]. However, there was no antimicrobial effect against Pseudomonas aeruginosa [ 17 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donkey milk kefir reduced Klebsiella pneumoniae , Bacillus cereus , and Proteus mirabilis by 8%, 37%, and 58% compared to the kanamycin antibiotic. In contrast, cow milk kefir decreased B. cereus by 12.9% while had the same impact on Proteus mirabilis compared to kanamycin, demonstrating the tremendous antimicrobial potential associated with lactic acid [ 60 , 66 ]. However, there was no antimicrobial effect against Pseudomonas aeruginosa [ 17 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, cow milk kefir decreased B. cereus by 12.9% while had the same impact on Proteus mirabilis compared to kanamycin, demonstrating the tremendous antimicrobial potential associated with lactic acid [ 60 , 66 ]. However, there was no antimicrobial effect against Pseudomonas aeruginosa [ 17 , 60 ]. Other organic acids present in kefir, such as acetic and pyruvic acid, also demonstrated an antimicrobial effect when administered together with lactic acid [ 14 , 31 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the studies examining the antimicrobial activity of donkey milk against S. aureus were checked; In a study conducted by Yirmibeşoğlu and Öztürk in 2020 they examined the zone diameters of donkey milk-impregnated discs against S. aureus, they found this zone diameter to be 11,5 mm, and the ampicillin zone diameter they added for control purposes was 22 mm [7]. In Koutb et al's study in 2016, they found that donkey milk-impregnated discs formed a zone diameter of 18 mm against S. aureus ATCC 8095, and the minimum lethal concentration was 64 when they examined it [8].…”
Section: Resultsmentioning
confidence: 99%
“…Control of MRSA is still an important problem in hospitals [5]. In some studies, it has been reported that donkey milk have different levels of antimicrobial activity against S. aureus strains [7,8]. Therefore, we aimed to examine the effectiveness of different dilution rates of donkey milk against S. aureus strains, which is an important problem all over the world, and to determine the antimicrobial effect of standard MRSA and MSSA strains in-vitro [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde eşek sütünün sağlık açısından kabul kriterleri bulunmadığından, eşek sütü üretiminin standartlaştırılması, ürün kalite kontrolünün güçlendirilmesi, tüketici ve işletmelerin haklarının korunması için uygun standartların belirlenmesi gerekmektedir. Son yıllarda eşek sütü ve ürünlerinin (kefir vs.) mikrobiyolojik profili ve riskleri, biyoaktiviteleri ve fizikokimyasal özellikleri ile ilgili yapılan çalışmalar artsa da endüstrisinin gelişimini sağlayacak verilerin toplanması adına daha fazla çalışmanın yapılması gerekmektedir [3,[7][8][9][10].…”
unclassified